Pobreza y política social en Colombia - Fresneda, Óscar (El Colegio de México A.C., 1998)
This work presents the scope and evolutionary trends of poverty in Colombia, and reviews the programs designed to struggle against it. The main premise is that the evolution of poverty and the factors that have determined its behavior in the past decades are essentials for defining adequate struggle policies. In the first part of his work, the author develops two methodological approaches for measuring poverty in Colombia, pl (income or poverty lines) and ubn (unsatisfied basic needs), and presents detailed data of its evolution, both generally and in particular metropolitan zones. In the second part, he reviews social policies for overcoming poverty, specially those presented after 1986, during the presidencies of Barco, Gavina, and Samper. He refers to sectors such as housing, basic public services, and employment, trying to point out how some of these policies manage to reduce poverty, particularly the one measured by UBN.